Citation report: the nightmares and dreams of the editor: we grew 30% - Rocha, Eduardo M.; Lira, Rodrigo Pessoa Cavalcanti; Schellini, Silvana Artioli [UNESP]; Antunes-Foschini, Rosalia (GN1 Sistemas e Publicacoes, 2021)
The publication of the Citation Report and its most relevant number, the Journal Impact Factor (JIF), by Journal Citation Reports (JCR) in the Web of Science, which is sponsored by Clarivate Analytics, is a medium-term evaluation of scientific journals. The JIF is an index calculated by dividing the number of citations of the articles published in the JCR year “y” by the total number of citable articles published in the two previous years
Relatório de citação: os pesadelos e sonhos do editor: crescemos 30%